Avaliação da atividade induzida pela Jack Bean Urease (JBU) sobre o sistema nervoso de baratas da espécie Nauphoeta cinerea - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The urease of Canavalia ensiformis (Jack bean urease, JBU) has been characterized as exhibiting a entomotoxic activity. Although several studies have already been performed aiming the study of this compound in different models of insects, few or none have demonstrated the exact mechanism of action of this compound on the cockroach nervous system. In this work we used the cockroach Nauphoeta cinerea as a experimental model in order to investigate the actions induced by JBU at central and peripheral nervous system and its mechanisms. We have performed a lethality assay, as well as a biochemical analysis to determine the activity of the urease on the insect brain cholinesterase. Biological models in situ and in vivo were also used in order to determine the sensitivity of different physiological systems to the compound, such as the technique of semi-isolated heart, the abductor-metatoraxic coxal muscle preparation in vivo and the measurement of grooming activity. The assays for the determination of the minimum lethal dose demonstrated that JBU (1.5, 3, 6μg/g of animal) is not lethal to N. cinerea, despite the animals became lethargic after 24h the administration of the compound. Such result can be explained by the absence of cathepsin-like enzymes in the digestive system of N. cinerea, or because we have administrated the urease by the circulatory system of the animals. The assays for determining the AChE activity, using the same doses, demonstrated that JBU significantly inhibited this enzyme (20±2%, 65±2% and 75±3%). The effects of JBU (1.5, 3 and 6μg/g animal) upon the insect heart rate, showed a positive chronotropic effect that was 94 ± 5bat./min in the saline control group, and 125±3bat./min with the administration of (3μg/g of animal) JBU. In this set of experiments the addition of neostigmine (5μM) mimicked the positive chronotropic effect induced by the urease which was also inhibited by atropine (1μM). The recordings of muscle twitch tension of the cockroaches treated with JBU (1.5, 3, 6μg/g of animal), showed that the urease induces an irreversible neuromuscular blockade (30±10%, 15±4% and 70±7%), respectively. The administration of acetylcholine (50μg/g of animal) or hydroxylamine (1μg/g of animal) mimicked the effect of the ureasealone at neuromuscular junctions, suggesting the involvement of the neurotransmitter Ach in the modulatory activity induced by JBU at cockoach peripheral nervous system. Therefore, the pretreatment of the animals with 11 dexamethasone (40μg/g of animal) partially inhibited the neuromuscular blocking activity of JBU (~75%), suggesting that part of the effect of the urease at insect neuromuscular junctions involves pro-inflammatory compounds. It was shown that the blockage of GABA receptors by bicuculline (5μg/g of animal), prevents JBUinduced neuromuscular activity (~50%), suggesting that the neurotransmitter GABA is involved in the peripheral inhibitory actions of the urease. The analysis of grooming behavior, that is characterized by the cleaning of front legs and antennas, showed that the control value for this assay was (153±8s/30min of legs and 70±6s/30min for the antennas) and after treatment with urease (1.5, 3, 6μg / g of animal) there was a significant increase in frequency of leg events (177±23s/30min, 253±33s/30min and 363±23s/30min), but not the antenna. The incubation of the animals with octopamine (15μg/g of animal) mimicked the effect induced by the urease, suggesting an activity related to this neurotransmitter. The pretreatment of the animals with phentolamine (0.1μg/g of animal) prevented the urease-increasing rate of leg grooming, suggesting a direct action at the octopamine receptor. The results reinforce the potential of ureases as natural insecticides showing the complexity of the mechanisms involved in the neurotoxicity of this compounds at the nervous system of cockroaches. The anticholinesterasic activity of JBU is not sufficient to produce the death of the animals, as do chemical organophosphate insecticides, but favors the development of important behavioral alterations.
Keywords: Urease; Canavalia ensiformis; Barata; Atividade anticolinesterásica; Bloqueio neuromuscular; Grooming; Cockroach; Acetylcholinesterase activity; Neuromuscular blockade; CNPQ::CIENCIAS BIOLOGICAS